Comparing Argentina and Australia (1880s-1960s): State Finances and Investments in Education and Health. Issue 1 (2nd January 2021) - Levy, James; Ross, Peter
ABSTRACT: Since the late nineteenth century, comparisons of Argentina and Australia have been common as both countries had and have similar economies based on the export of commodities and the importation of migrants, finance and technology. By the 1970s it was apparent that in general Australians had a higher standard of living than did Argentines. In this article we argue that at least in part this was due to there being a more interventionist State in Australia, which raised more revenues per capita than did the Argentine State, and invested more heavily and more effectively in the development of societal capital including in the areas of education and health. This finding supports recent arguments from such multilateral organizations as the World Bank that investment in human capital, especially education but also health, generates economic and social development, and that this investment is predicated on government intervention.